Breast/Mammella (C50.9) - The accuracy of sentinel lymph-node biopsy in breast cancer after previous excisional biopsy / L’accuratezza del linfonodo sentinella dopo biopsia escissionale del carcinoma della mammella - Marrazzo, A.; Taormina, P.; Marrazzo, et al., E. (European Journal of Oncology and Environmental Health, 2013)
Aim: Sentinel node  biopsy (SLNB) is considered to be the standard of care for staging the axilla in clinically node-negative women with breast cancer. A previous breast excisional biopsy has been considered a contraindication to the use of SLNB. We examined the success rate of SLN localization and then the evaluation of the incidence of axillary relapse in patients with breast cancer undergoing excisional biopsy. Patients and Methods: 858 patients with breast carcinoma underwent a SLNB and only positive sentinel nodes were submitted to axillary dissection; 82 patients had undergone an excisional biopsy before. Results: The sentinel node was identified in 100% of cases, it was negative in 74.4% and positive in 23.1%. Complete axillary dissection was performed in all positive cases, and in 74% of cases no other positive nodes were found. The follow-up median was 63.5 months and no axillary recurrence was observed. Conclusions: SLNB accuracy in breast cancer patients who have previously undergone excisional biopsy is comparable with that in patients undergoing no excisional biopsy, so that it may be considered a standard procedure.L’accuratezza del linfonodo sentinella dopo biopsia escissionale del carcinoma della mammellaScopo: La biopsia del linfonodo sentinella  (BLS) nel carcinoma della mammella con linfonodi ascellari clinicamente negativi è considerato  la migliore scelta per stadiare il cavo ascellare. Inizialmente una precedente biopsia escissionale del carcinoma era considerata una controindicazione. Esaminiamo il tasso di successo della BLS e la incidenza della recidiva a livello ascellare in pazienti con carcinoma della mammella precedentemente sottoposti a biopsia escissionale del tumore. Pazienti e metodi: 858 pazienti con carcinoma della mammella sono stati sottoposti a BLS e i pazienti con linfonodi sentinella metastatici a svuotamento del cavo ascellare; 82 pazienti erano stati sottoposti precedentemente a biopsia escissionale del tumore. Risultati: Il linfonodo sentinella è stato identificato nel 100% dei casi, è risultato indenne nel  74,4% e metastatico nel 23,1%. La dissezione del cavo ascellare è stata effettuata in tutti i casi con linfonodi sentinella metastatici e nel 74% dei casi non si sono ritrovati altri linfonodi ascellari metastatici. Il follow-up mediano è stato di 63,5 mesi e non si sono osservate recidive ascellari. Conclusioni: L’accuratezza del BLS in pazienti con carcinoma della mammella sottoposte precedentemente a biopsia escissionale  è uguale a quella dei pazienti non sottoposti a biopsia.